(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
As a popular deep learning method for processing image information, convolutional neural networks can learn the features in the image after training, and complete the extraction and classification of image features. Therefore, it is widely used in the research of computer vision fields such as picture processing and pattern recognition. The purpose of this article is to sort out convolutional neural networks and their structural characteristics and introduce and analyze the basic working principles of convolutional neural networks and realize examples of the application of CNN model training in image feature extraction and recognition.